The hundred languages of children : the Reggio Emilia experience in transformation - Edwards, Carolyn P.; Gandini, Lella; Forman, George E., 1942- (Praeger, 2012)
"Why does the city of Reggio Emilia in northern Italy feature one of the best public systems of early education in the world? This book documents the comprehensive and innovative approach that utilizes the "hundred languages of children" to support their well-being and foster their intellectual development"--